2017
DOI: 10.1103/physreve.96.022136
|View full text |Cite
|
Sign up to set email alerts
|

Survival probability in a quenched Majorana chain with an impurity

Abstract: We investigate the dynamics of a one-dimensional p-wave superconductor with next-nearest-neighbor hopping and superconducting interaction derived from a three-spin interacting Ising model in transverse field by mapping to Majorana fermions. The next-nearest-neighbor hopping term leads to a new topological phase containing two zero-energy Majorana modes at each end of an open chain, compared to a nearest-neighbor p-wave superconducting chain. We study the Majorana survival probability (MSP) of a particular Majo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Examples of other problems discussed with the use of the LMT or the Lieb-Schultz-Mattis theorem can be found in Refs. [7][8][9][10][11][12][13][14]. On the other hand, there are many attempts to extend these theorems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of other problems discussed with the use of the LMT or the Lieb-Schultz-Mattis theorem can be found in Refs. [7][8][9][10][11][12][13][14]. On the other hand, there are many attempts to extend these theorems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of edge states under a sudden quantum quench has been investigated in two-dimensional topological insulator [36], where it was shown that, in the abrupt transition from the topological insulator to the trivial insulator phase, there is a collapse and revival of the edge states [30,34]. Similar results have been obtained for the one-dimensional Kitaev model [31,32,37,38].…”
Section: Introductionmentioning
confidence: 56%
“…Very recently, the studies of the connection between quenching dynamics and quantum phase transition [5,12,20], the topological order [26][27][28] and also the dynamics of an edge state [29][30][31][32], have attracted the attention of the scientists. Specifically, searching the robustness and response of the topological edge states to quantum quenches [28,31,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations